The Feldstein–Horioka Puzzle and Structural Breaks: Evidence from the Largest Countries of Asia. (August 2016) - Ketenci, Natalya
The purpose of this article is to investigate the level of capital mobility in the largest economies of Asia by testing the Feldstein–Horioka puzzle. Panel estimations using quarterly data for the period from 1995 to 2011 have been made for the seven largest economies of Asia, specifically Russia, Japan, South Korea, Turkey, India, Indonesia and China. This group of countries has gained significant economic power in the world over the last decade. Specifically, the growth rates of the sample has for a long period of time exceeded the growth rates of most developed countries. The total GDP adjusted for PPP is far above of the GDP of the European Union and NAFTA groups and very close to the G7 group. The article examines changes in investment savings relationships when the presence of structural shifts—where such exist—is taken into account. Recently developed panel techniques are employed to examine the investment–savings relationship and estimate saving–retention coefficients. As a result of these estimations, countries were divided into two groups consisting of stable and unstable economies. This division of countries allows for more precise estimates of capital mobility. The empirical findings reveal the existence of the moderate level of capital mobility in the group. Results indicate that countries with relatively higher capital mobility are exposed to the negative effects of international market fluctuations. JEL Classification: F32